2012
DOI: 10.1186/1940-0640-7-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial evaluating an mHealth system to monitor and enhance adherence to pharmacotherapy for alcohol use disorders

Abstract: BackgroundNonadherence to prescribed medication regimens is a substantial barrier to the pharmacological management of alcohol use disorders. The availability of low-cost, sustainable interventions that maximize medication adherence would likely lead to improved treatment outcomes. Mobile health (mHealth) technologies are increasingly being adopted as a method of delivering behavioral health interventions and represent a promising tool for adherence interventions. We are evaluating a cell-phone–based intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
1
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
0
19
1
4
Order By: Relevance
“…With advances in computing technology, a number of researchers have developed interventions that can be administered on electronic devices (Rizvi, Dimeff, Skutch, Carroll, & Linehan, 2011; Stoner & Hendershot, 2012; Watts et al, 2013). There are many advantages of computerized interventions, including 24-hour availability, anonymity, portability, increased compliance, and accurate data recording (Heron & Smyth, 2010).…”
Section: The Promise Of Mobile Interventionsmentioning
confidence: 99%
“…With advances in computing technology, a number of researchers have developed interventions that can be administered on electronic devices (Rizvi, Dimeff, Skutch, Carroll, & Linehan, 2011; Stoner & Hendershot, 2012; Watts et al, 2013). There are many advantages of computerized interventions, including 24-hour availability, anonymity, portability, increased compliance, and accurate data recording (Heron & Smyth, 2010).…”
Section: The Promise Of Mobile Interventionsmentioning
confidence: 99%
“…A few studies evaluated the effect of mobile telephone-based interventions on medication adherence 1720. Two randomized controlled trials demonstrated that integration of mobile telephone intervention into antiretroviral therapy management improved patients’ adherence to therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Fatores de Não Adesão 1. Efeitos colaterais e adversos da medicação (12,15,18,20,22,26,32,40,41) 2. Longo tempo de tratamento medicamentoso (11,15,33,36,38,(42)(43)(44)(45) 3.…”
Section: Dimensão Tratamentounclassified